A COMPARATIVE ANALYSIS BETWEEN PHOSPHATES AND SILICATES-BASED DENTIFRICE TOOTHPASTES - Laura Ecaterina Romila; Alina Monica Miftode; Ionut Iulian Lungu; Daniela Ivona Tomita; Mihaela Papusa Vasiliu; Diana Gheban; Norin Forna; Constanta Mocanu; Alina Stefanache (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: Toothpaste, an indispensable component of oral hygiene routines, has witnessed a remarkable evolution from ancient times to the present era of scientific rigor. This study explores the differences in toothpaste formulations, focusing on the integration of active compounds, abrasive agents, stabilizers, and anticorrosive measures. Introduction: Historically, toothpaste, or dentifrice, has been utilized since antiquity, with various cultures employing diverse ingredients such as salt and plants for oral care. However, in the developed world, toothpaste has become universally adopted, with formulations ranging from cosmetic to medicinal classifications based on their preventive and therapeutic effects on oral health. Materials and methods: The development of toothpaste formulations involves meticulous experimentation to strike a balance between efficacy and safety. Key components include active compounds like sodium fluoride, abrasive agents such as dicalcium dihydrate phosphate, and stabilizers like Aerosil and Sident. Results: These ingredients are carefully selected to optimize cleaning efficacy while minimizing risks such as enamel abrasion and corrosion in packaging materials. This study highlights emerging trends in toothpaste formulation, including the integration of nanotechnology for enhanced anticorrosive measures, exploration of biodegradable alternatives, and customization of formulations to meet individual preferences. Advanced manufacturing techniques such as 3D printing enable precise control over ingredients, paving the way for personalized oral care solutions. Conclusion: In summary, the continuous refinement of toothpaste formulations underscores a commitment to improving oral health outcomes while addressing sustainability and personalized care demands. By embracing these advancements, the dental industry can contribute to promoting overall well-being and enhancing oral hygiene practices on a global scale.